High serum IL-17A is associated with bone destruction in newly diagnosed multiple myeloma patients - Dong, Mengmeng; Zhang, Jinna; Chen, Qingxiao; He, Donghua; Yan, Haimeng; Zheng, Gaofeng; Han, Xiaoyan; He, Jingsong; Cai, Zhen (Frontiers in Oncology, 2022)
Background Multiple myeloma (MM) is a malignant proliferative disease of the blood system, characterized by the abnormal growth of clonal plasma cells in the bone marrow. The bone marrow microenvironment (BMM) is highly critical in the pathological process of MM. Many studies have shown that serum interleukin-17A (IL-17A) plays a key role in various infectious diseases, autoimmune diseases, and cancers. However, more clinical studies need to be performed to further prove the influence of serum IL-17A levels on multiple myeloma patients. Methods Among a total of 357 participants in our institution’s MM cohort, 175 were eligible for the retrospective study. Multivariate regression models adjusted by potential confounding factors, the violin plots, the generalized additive model and smooth curve fittings, receiver operating characteristic (ROC) curve, and Kaplan–Meier (K-M) curve analysis were applied to the research. Results A total of 175 patients with newly diagnosed MM were enrolled in this study. The multivariate linear regression analysis showed that serum IL-17A level in MM patients correlated with the degree of bone lesions and fracture incidence (fully adjusted model, pbone lesion < 0.0001, pfracture < 0.0001). The violin plot showed that MM patients with higher serum IL-17A levels had more severe bone lesions and higher fracture incidence than those with lower serum IL-17A levels. A total of 171 patients were included in the study of the relationship between serum IL-17A and best overall effect (BOE). We found that serum IL-17A levels were independently related to the best inductive therapeutic efficacy (fully adjusted model, p = 0.037), and the relationship was especially obvious in the light chain group (fully adjusted model, p = 0.009) and IgA group (fully adjusted model, p = 0.0456). It could be deduced from the smooth curve that the higher the serum IL-17A level, the worse the BOE (p = 0.0163). The ROC prediction curve suggested that serum IL-17A could predict the BOE to a certain extent (area under the curve (AUC) = 0.717, p = 0.0327). A total of 148 MM patients were observed in the longitudinal study of the relationship between serum IL-17A and progression-free survival/overall survival (PFS/OS). The K-M curve analysis indicated that serum IL-17A levels in MM patients were not significantly correlated with PFS and OS. However, in the light chain subgroup, MM patients with high serum IL-17A had worse PFS (p = 0.015) and OS (p = 0.0076) compared to those with low serum IL-17A. In the IgA type subgroup, the higher IL-17A level was related to worse OS (p = 0.0061). Conclusion This retrospective study found that higher levels of serum IL-17A were independently correlated with higher severity of bone disease and fracture incidence in newly diagnosed MM patients. High serum IL-17A level was related to poor best overall efficacy in the light chain type. High serum IL-17A was also associated with poor PFS and OS in the light chain type and OS in the IgA type subgroup.